2019
DOI: 10.1111/1462-2920.14806
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐resolved metagenomics and metatranscriptomics reveal niche differentiation in functionally redundant microbial communities at deep‐sea hydrothermal vents

Abstract: Summary The structure and function of microbial communities inhabiting the subseafloor near hydrothermal systems are influenced by fluid geochemistry, geologic setting and fluid flux between vent sites, as well as biological interactions. Here, we used genome‐resolved metagenomics and metatranscriptomics to examine patterns of gene abundance and expression and assess potential niche differentiation in microbial communities in venting fluids from hydrothermal vent sites at the Mid‐Cayman Rise. We observed simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 57 publications
2
51
2
Order By: Relevance
“…Indeed, we observed a partition of metabolic diversity among the steep environmental gradients on Deception Island. Unlike previous studies carried out at hydrothermal vents which pointed to metabolic functional redundancy at the community level (Galambos et al, 2019;Reveillaud et al, 2016), Deception communities showed metabolic heterogeneity across the sharp temperature gradient. The observation of functional redundancy despite the taxonomic variation has been observed in several environments such as venting fluids from the Mariana back-arc, cold subseafloor ecosystems, freshwater and gut microbiomes (Louca et al, 2016;Trembath-Reichert et al, 2019;Tully et al, 2018;Turnbaugh and Gordon, 2009;Várbíró et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, we observed a partition of metabolic diversity among the steep environmental gradients on Deception Island. Unlike previous studies carried out at hydrothermal vents which pointed to metabolic functional redundancy at the community level (Galambos et al, 2019;Reveillaud et al, 2016), Deception communities showed metabolic heterogeneity across the sharp temperature gradient. The observation of functional redundancy despite the taxonomic variation has been observed in several environments such as venting fluids from the Mariana back-arc, cold subseafloor ecosystems, freshwater and gut microbiomes (Louca et al, 2016;Trembath-Reichert et al, 2019;Tully et al, 2018;Turnbaugh and Gordon, 2009;Várbíró et al, 2017).…”
Section: Discussioncontrasting
confidence: 99%
“…Among extreme marine systems, hydrothermal vents have wide global distribution, occurring in all oceanic bottoms, at different latitudes and depths and harboring rich and peculiar biological communities (Parson et al, 1995;Dando et al, 2000). Several studies revealed that the occurrence of benthic organisms in the hydrothermal systems is strongly related to the volcanic fluids that outflow from the bottom, characterized by high concentrations of iron, zinc sulfides and gases, such as CH 4 , H 2 S, H 2 , and CO 2 (e.g., Van Dover and Fry, 1989;Micheli et al, 2002;Hall-Spencer et al, 2008;Martin et al, 2008;Yao et al, 2010). A great biological difference occurs between deep and shallow vents.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study [6], we observed that several genera, including Cellvibrio, showed significantly higher relative abundance in the rhizoplane microbiome, a niche characterized by more intimate host-microbe interactions, compared with the rhizosphere microbiome, and the mechanisms underlying their rhizosphere-to-rhizoplane enrichment were further revealed at the whole microbial community level. Recent developments on MAG recovery and analysis methods enabled us to perform genome-centric analyses on the structure and function of the microbiome, which can provide more detailed and accurate information to reveal the mechanisms underlying niche adaptation of microbes compared with whole community-based analyses [37][38][39]. To gain a better understanding of the strategies used by the adapted microbes for the citrus rhizosphere-to-rhizoplane enrichment, we sought to recover MAGs from the metagenome data and compare the gene expression profiles of the MAGs between the rhizosphere and rhizoplane niches.…”
Section: Recovery and Curation Of The Almost Complete Metagenome-assementioning
confidence: 99%